2017
DOI: 10.1242/dev.146811
|View full text |Cite|
|
Sign up to set email alerts
|

Epigenetic resetting of human pluripotency

Abstract: Much attention has focussed on the conversion of human pluripotent stem cells (PSCs) to a more naïve developmental status. Here we provide a method for resetting via transient histone deacetylase inhibition. The protocol is effective across multiple PSC lines and can proceed without karyotype change. Reset cells can be expanded without feeders with a doubling time of around 24 h. WNT inhibition stabilises the resetting process. The transcriptome of reset cells diverges markedly from that of primed PSCs and sha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
309
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 249 publications
(330 citation statements)
references
References 97 publications
21
309
0
Order By: Relevance
“…A cohort of genes enriched in human preimplantation epiblast cells is highly expressed in naïve but not in primed hPSCs (Figure ) . There is a considerable range in the expression levels of naïve‐associated genes when comparing between various naïve hPSCs lines derived in different conditions, indicating that some conditions are better than others at recapitulating the transcriptional programmes of human epiblast cells . Additionally, genes such as KLF4 and TFCP2L1 are sensitive to perturbation only in naïve hPSCs, suggesting a rewiring in gene regulatory circuitries and dependencies has occurred between naïve and primed pluripotent states .…”
Section: A Molecular Framework To Guide Human Pluripotent State Charamentioning
confidence: 91%
“…A cohort of genes enriched in human preimplantation epiblast cells is highly expressed in naïve but not in primed hPSCs (Figure ) . There is a considerable range in the expression levels of naïve‐associated genes when comparing between various naïve hPSCs lines derived in different conditions, indicating that some conditions are better than others at recapitulating the transcriptional programmes of human epiblast cells . Additionally, genes such as KLF4 and TFCP2L1 are sensitive to perturbation only in naïve hPSCs, suggesting a rewiring in gene regulatory circuitries and dependencies has occurred between naïve and primed pluripotent states .…”
Section: A Molecular Framework To Guide Human Pluripotent State Charamentioning
confidence: 91%
“…We used five datasets containing transcriptome profiles of 23 naive and 15 primed state human embryonic stem cell samples in our study ( Table 1). The included naive samples were generated by different methods including those by forced expression of pluripotency TFs [14], by the use of small molecule and/or growth factors in culture medium [7,15,16] and direct derivation from an embryo [17]. The datasets were identified based on the criteria that each dataset contained both naive and primed state samples.…”
Section: Data Retrievalmentioning
confidence: 99%
“…KLF4 and another blue module hub transcription factor TFCP2L1 are a part of the core gene regulatory network of naive pluripotency in mESC [48]. ZNF534 is a negative regulator of the human endogenous retrovirus HERVH which in turn has a key regulatory role in human PSCs [17]. SALL1 and SALL2 are key regulators of organogenesis [49].…”
Section: Transcription Factor Screening Among Intra-modular Hub Genesmentioning
confidence: 99%
“…These observations lead to the question of whether the hypomethylated epigenome reflects the biology of the preimplantation human embryo and is an informative readout of the naive state, or alternatively, is it a direct effect of MEK1/2 inhibition that simply mimics our expectations? Comparing the methylomes between naive hESCs and human embryos reveals similar levels of low, global DNA methylation [11,13,17]. However, a closer examination of methylation levels at CpG sites between naive hESCs and human embryos showed that the methylomes are actually quite different; naive hESCs have fairly uniform and low levels across the genome, whereas the embryo retains regions with higher levels of DNA methylation [17].…”
mentioning
confidence: 95%
“…Several reports of preimplantation-like human stem cells, broadly termed 'naive' hESCs, have raised the hope that deriving such a cell type is achievable [6][7][8][9][10][11]. These recent additions to the stem cell hierarchy are particularly exciting for developmental epigeneticists.…”
mentioning
confidence: 99%